Recent advances of non-invasive diagnostic modalities for type 2 diabetic kidney disease - Chao-jing Ma; Chan-juan Ma (Editorial Department of Journal of Clinical Nephrology, 2024)
As a highly prevalent disease worldwide, diabetes kidney disease （DKD） is a common complication of diabetes and a major cause of end-stage renal disease （ESRD）. One clinical symptom of DKD is persistent proteinuria with or without a gradual decrease in glomerular filtration rate （GFR）. Urinary microalbumin is currently recognized as a marker of early renal injury. However, it has some limitations. Kidney biopsy is a gold diagnostic standard for DKD. Yet its wider applications are restricted by its invasive nature. Therefore actively seeking non-invasive and reliable diagnostic modalities for DKD is of great significance. This review summarized the latest researches of early non-invasive diagnosis of DKD and provided valuable references for an early diagnosis of DKD in clinical practices.